Architecture selection for 5G-radio access network using type-2 neutrosophic numbers based decision making model - Abdullah Hussein Abdullah Al-Amoodi (Tanjong Malim, 2024)
Architecture selection for 5G-radio access network using type-2 neutrosophic numbers based decision making model by Abdullah Hussein Abdullah Al-Amoodi